Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1155/2019/2348165
|View full text |Cite
|
Sign up to set email alerts
|

Increased Transfection of the Easily Oxidizable GC-Rich DNA Fragments into the MCF7 Breast Cancer Cell

Abstract: Objective. Easily oxidizable GC-rich DNA (GC-DNA) fragments accumulate in the cell-free DNA (cfDNA) of patients with various diseases. The human oxidized DNA penetrates the MCF7 breast cancer cells and significantly changes their physiology. It can be assumed that readily oxidizable GC-DNA fragments can penetrate the cancer cells and be expressed.Methods. MCF7 cells were cultured in the presence of two types of GC-DNA probes: (1) vectors pBR322 and pEGFP and (2) plasmids carrying inserted human rDNA (pBR322-rD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…apoptosis levels, glucose consumption rate, proliferation rate, cell cycle phase, etc.). 4,[11][12][13][14][15] Consequently, the concentration and size of cfDNA measured at any instance may differ significantly for a single cell line and between cell lines. For example, some cell lines may be characterized by a low concentration of high molecular weight cfDNA, while others may be characterized by a high concentration of low molecular weight DNA.…”
Section: Resultsmentioning
confidence: 99%
“…apoptosis levels, glucose consumption rate, proliferation rate, cell cycle phase, etc.). 4,[11][12][13][14][15] Consequently, the concentration and size of cfDNA measured at any instance may differ significantly for a single cell line and between cell lines. For example, some cell lines may be characterized by a low concentration of high molecular weight cfDNA, while others may be characterized by a high concentration of low molecular weight DNA.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have shown that the ability of oxidatively damaged cfDNA to be transferred into human cancer and stem cells significantly depends on their oxidative modifications [14, 24, 25, 27] and identified signaling pathways, activated by oxidized cfDNA in different human cells [14, 18, 25, 31]. We suggested that oxidized cfDNA, produced by dying cells under endogenous or exogenous oxidative stress, is able to be transferred into neurons and glial cells, activating signaling pathways genes.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have shown that oxidized cfDNA penetration into the cells is accompanied by the induction of the reactive oxygen species (ROS) synthesis [14, 24, 25, 27] that may lead to the oxidatively generated DNA modifications in cultured cells. An addition of oxidized cfDNA fragments (concentration 50 ng/mL, cultivation time 2 h) to the culture medium increases the 8-oxodG level in cultured cells by 5-6 times ( p < 0.001; Figure 3(a)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A question whether plasmid DNA requires linearization before adding to the culture medium was considered earlier (45). Our tests failed to show any difference between the rates of accumulation of intact GC-DNAs and their linearized forms in the cells.…”
Section: Methodsmentioning
confidence: 99%